2018
DOI: 10.1590/0001-3765201720150557
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of Aphis gossypii Glover and in sole and intercropping systems of cotton and cowpea

Abstract: Population dynamics of aphids have been studied in sole and intercropping systems. These studies have required the use of more precise analytical tools in order to better understand patterns in quantitative data. Mathematical models are among the most important tools to explain the dynamics of insect populations. This study investigated the population dynamics of aphids Aphis gossypii and Aphis craccivora over time, using mathematical models composed of a set of differential equations as a helpful analytical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The predominance of A. gossypii and P. solenopsis populations in cotton fields respectively during south-west and post-monsoon seasons are not surprising. In fact, it is known that the population dynamics of aphids and mealybugs can be affected by seasonal changes in weather conditions 37 . Moreover, Wang et al 38 showed that high rainfall was unfavourable for serious infestation by P. solenopsis.…”
Section: Discussionmentioning
confidence: 99%
“…The predominance of A. gossypii and P. solenopsis populations in cotton fields respectively during south-west and post-monsoon seasons are not surprising. In fact, it is known that the population dynamics of aphids and mealybugs can be affected by seasonal changes in weather conditions 37 . Moreover, Wang et al 38 showed that high rainfall was unfavourable for serious infestation by P. solenopsis.…”
Section: Discussionmentioning
confidence: 99%